The effect of Schema- based couple therapy on marital satisfaction and emotional dysregulation in discordant couples: Single Subject Research - Bardikhoje, Azim; Jahangiri, Ali; Mafakheri, Abdollah (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The aim of this research was the effect of schema-based therapy on marital satisfaction and difficulty in emotional regulation, in discordant couples. Method: In term of its purpose, this research had a single-subject design with a pre-test, post-test and follow-up design. The statistical population included all conflicted couples who referred to Parsa counseling and psychotherapy clinic in Bandar Turkmen city in the second quarter of 2021, from which 3 couples (husband and wife) were selected by using targeted sampling. Data collection was done with demographic information checklist (researcher-made form), marital satisfaction scale (MSS), Olson et al. (1987) and Difficulties in emotional regulation scale (DERS), Gratz and Romer (2004). Subjects in one group received 12 sessiond each and two sessions per week for 90 minutes. Results: The finding of the research during the visual analisis of the data graph based on the indicators of descriptive statistics and visual analysis showed that in the follow-up phase compared to the baseline, the intervention in creased the total scores of marital satisfaction and decreased the scores of emotional dysregulation components except the component of the difficulty of purposeful behavior in the schema therapy method, treatment was significant (P < 0/05). Conclusion: The result of the research shows that schema therapy is effective in increasing marital satisfaction and reducing emotional maladjustment of conflicting and discordant couples and it be used in treatment centers to improve family and marital functioning.